Prevalence and prognostic value of left ventricular late gadolinium enhancement in patients with idiopathic outflow tract ventricular arrhythmias. (25th November 2020) - Nucifora, G; Muser, D; Castro, S; Casado Arroyo, R; Benhayon, D; Liuba, I; Sadek, M; Magnani, S; Callans, D; Frankel, D; Marchlinski, F; Santangeli, P
Abstract: Background: Patients with idiopathic outflow tract ventricular arrhythmias (OTVAs) and structurally normal heart by ECG and echocardiogram often undergo cardiac magnetic resonance (CMR) study to evaluate for presence of concealed myocardial abnormalities with late gadolinium enhancement (LGE). However, the clinical impact of incidental LGE finding in the left ventricle (LV) in patients with idiopathic OT-VAs is unclear. Accordingly, the aim of the present study was to investigate the prevalence, characteristics and prognostic significance of isolated LV LGE in a large population of patients with OTVA undergoing CMR. Methods: A total of 364 consecutive patients (43±16 years, 53% male) with OTVA and negative routine diagnostic work-up were included. All patients underwent a CMR study with LGE imaging for detection of scar/replacement fibrosis. Presence of LGE was correlated with long term major adverse cardiovascular events including sudden cardiac death (SCD), resuscitated cardiac arrest and nonfatal documented sustained ventricular tachycardia. Results: Isolated LGE in the LV was identified in 15 patients (4%), typically involving the inferolateral wall (11 cases, 73%) and having a median extension of 3 (2–5)% of the LV mass. All cases showed a midmyocardial/subepicardial distribution consistent with a possible prior myocarditis. Patients with incidental finding of LV-LGE were older (55±13 years vs. 42±16 years; p<0.01) and were more frequently males (80% vs. 51%; p=0.03). After a median follow-up of 69 (47–98) months, none of the patients in the LV-LGE group and 1 patient (0.3%) in the non-LGE group (p=1.0) experienced the composite end-point which consisted in an episode of sustained VT with hypotension and dizziness. The patient subsequently underwent effective radiofrequency ablation of the VT from the right ventricular outflow tract. Conclusion: In this large CMR study, isolated LV scar was found in 4% of patients with idiopathic OT-VAs, was small in size with distribution consistent with prior myocarditis. The LGE abnormality did not portend a negative prognosis. Funding Acknowledgement: Type of funding source: None